Growth Hormone and Endometrial Receptivity - Altmäe, Signe; Aghajanova, Lusine (Frontiers in Endocrinology, 2019)
Administration of growth hormone (GH) during ovarian stimulation has shown beneficial effects on in vitro fertilization (IVF) outcomes. It is generally believed that this improvement is due to the stimulating effect of GH on oocyte quality. However, studies are emerging that show possible positive effect of GH administration on endometrial receptivity, thus suggesting an additional potential benefit at the level of the uterus, especially among women with recurrent implantation failure, thin endometrium, and older normal responders. This review summarizes recent data on GH co-treatment effects on endometrium and endometrial receptivity among infertile women undergoing IVF, and proposes possible mechanisms of GH actions in the endometrium.